Защита от коррозии деталей ранцевых установок пожаротушения композиционными покрытиями на основе сплава Cu-Ni1. Разработка методов электрохимического синтеза томпаковых покрытий и зависимость их состава от условий получения - Reva, Ольга; Mikhalyuk, Сергей; Bogdanova, Валентина (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2012)
New stable poly ligand solution for Cu-Ni allow electrodepositing with high buffer capacity and absence of cathode passivation is developed. The research of dependence the chemical compound of Cu-Ni films, synthesized by electrochemical sedimentation from poly ligand solution, from conditions of synthesis is carried out. The ways of regulation the components maintenance in an alloy are develop, the application of Cu-Ni allow films for corrosion protection the fire extinguishing units is based.